FOLLICULAR DEVELOPMENT AND THE ONSET OF ESTRUS DUE TO INDUCTION OF GNRH IN BALI CATTLE ANESTRUS POSTPARTUM WITH DIFFERENT BODY CONDITION SCORE - Widiarta, I Nyoman Oka; Pemayun, Tjok Gde Oka; Trilaksana, I Gusti Ngurah Bagus (Buletin Veteriner Udayana, 2020)
This study aim to determine the development of follicles and onset of estrus due to GnRH induction in bali cattle which has anestrus postpartum more than three month with differnt body condition score in the Badung regency of Bali.The designd used in this study was a complete random design  were divided into three treatment groups, namely Group 1 : cattle with BCS 2, Group 2  : cattle with BCS 3, Group 3  : cattle with BCS 4, each group consisted of 9 replication. All of group of bali cattle are induced by GnRH (Fertagyl, Intervet,Inc) at a dose of 500µg/IM/cattle. The result of this study indicate the development of follicles averages before induction of GnRH is 4.03 + 0.21 mm, 4.60 + 0.18 mm, 4.56 + 0.22 mm, each for BCS2, BCS 3 and BCS 4 and development of follicles averages after induction of GnRH is 7.08 + 0.42mm, 11.06 + 0.40 mm and 11.99 + 0.33  each for BCS 2, BCS 3 and BCS 4 and statistically shows that there are significant differences (P<0,05). The averages onset of estrus in the three treatment group is 7.75 + 0.89 day, 4.63 + 0.52 day dan 3.63 + 0.52day, each for BCS 2, BCS 3 and BCS 4 and statistically shows that there are significant differences (P<0,05).  The largest follicular diameter in BCS 4 is 11,99 + 0,33 mm with the time of onset of estrus 3,63 + 0,52 day. The result can be concluded that the induction of GnRH 500ug in bali cattle can increase follicular development and accelerate the oset of estrous.